2019
DOI: 10.1002/adhm.201900847
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Supramolecular Ureidopyrimidinone Hydrogels Provide Sustained Release of Extracellular Vesicle Therapeutics

Abstract: Extracellular vesicles (EVs) are small vesicles secreted by cells and have gained increasing interest as both drug delivery vehicles or as cell‐free therapeutics for regenerative medicine. To achieve optimal therapeutic effects, strategies are being developed to prolong EV exposure to target organs. One promising approach to achieve this is through EV‐loaded injectable hydrogels. In this study, the use of a hydrogel based on ureido‐pyrimidinone (UPy) units coupled to poly(ethylene glycol) chains (UPy‐hydrogel)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 49 publications
2
59
0
Order By: Relevance
“…[ 208 ] Additionally, injection of MSC‐CM encapsulated in a platelet‐rich plasma hydrogel ameliorated renal healing and function in an acute kidney injury model, [ 209 ] while MSC‐CM delivered in synthetic PLGA nanoparticles coated with red blood cell membranes enhanced liver regeneration. [ 210 ] Several studies have demonstrated the potential of biomaterial‐based delivery of MSC‐EVs [ 211 ] for repair in indications such as peripheral nerve injury, [ 212 ] epidural fibrosis, [ 213 ] and incisional hernia [ 214 ] ( Table 2 ). For example, EV‐functionalized polyethylene glycol hydrogels significantly enhanced hepatic regeneration in a chronic liver failure model compared to bolus EV injections by attenuating inflammation, apoptosis, and fibrosis.…”
Section: Biomaterials Functionalized With Msc Secretomementioning
confidence: 99%
“…[ 208 ] Additionally, injection of MSC‐CM encapsulated in a platelet‐rich plasma hydrogel ameliorated renal healing and function in an acute kidney injury model, [ 209 ] while MSC‐CM delivered in synthetic PLGA nanoparticles coated with red blood cell membranes enhanced liver regeneration. [ 210 ] Several studies have demonstrated the potential of biomaterial‐based delivery of MSC‐EVs [ 211 ] for repair in indications such as peripheral nerve injury, [ 212 ] epidural fibrosis, [ 213 ] and incisional hernia [ 214 ] ( Table 2 ). For example, EV‐functionalized polyethylene glycol hydrogels significantly enhanced hepatic regeneration in a chronic liver failure model compared to bolus EV injections by attenuating inflammation, apoptosis, and fibrosis.…”
Section: Biomaterials Functionalized With Msc Secretomementioning
confidence: 99%
“…As an example, ureido-pyrimidinone (UPy) poly(ethylene glycol) hydrogels were developed for prolonged exosome release at the target site while retaining their function. [131] As mentioned earlier, EVs are involved in tissue repair mechanisms, but when they are used therapeutically, their short lifetime at the site of injury is a limitation. It has been shown that repeated administration of EVs shows superior regenerative effects compared to a single administration of the same total EV concentration.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…hydrogels (Mol et al, 2019). Multiple hydrogen bonding units simultaneously act as hydrogen bond donors and acceptors.…”
Section: Ureido-4[1h]pyrimidinone (Upy)mentioning
confidence: 99%
“…During the 1990s, Meijer and his group described quadruple hydrogen bonding in building blocks 2-ureido-4[1H]pyrimidinone (UPy). This has been widely adopted as the force behind the development of supramolecular hydrogels ( Mol et al, 2019 ). Multiple hydrogen bonding units simultaneously act as hydrogen bond donors and acceptors.…”
Section: Supramolecular Hydrogels For Stem Cell Deliverymentioning
confidence: 99%